2019
DOI: 10.1096/fj.201801818r
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine exposure to hyperglycemia retards the development of brown adipose tissue

Abstract: Brown adipose tissue (BAT) is an exclusive tissue of nonshivering thermogenesis. It is fueled by lipids and glucose and involved in energy and metabolic homeostasis. Intrauterine exposure to hyperglycemia during gestational diabetes mellitus may result in abnormal fetal development and metabolic phenotypes in adulthood. However, whether intrauterine hyperglycemia influences the development of BAT is unknown. In this study, mouse embryos were exposed to the intrauterine hyperglycemia environment by injecting st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 72 publications
(83 reference statements)
1
14
0
Order By: Relevance
“…The effects of hyperglycemia are in rodent models partly mediated by epigenetic changes, being modifications of histones, DNA and noncoding RNAs ultimately influencing gene expression [102]. Indeed, maternal hyperglycemia is associated with increased DNA methylation in specific genes in offspring, inducing chronic effects for offspring development [103]. Furthermore, methylation-mediated epigenetic mechanisms for intergenerational susceptibility to metabolic disorders were found in a mouse model for GDM [104].…”
Section: Epigenetic Effects Of Maternal Obesity and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of hyperglycemia are in rodent models partly mediated by epigenetic changes, being modifications of histones, DNA and noncoding RNAs ultimately influencing gene expression [102]. Indeed, maternal hyperglycemia is associated with increased DNA methylation in specific genes in offspring, inducing chronic effects for offspring development [103]. Furthermore, methylation-mediated epigenetic mechanisms for intergenerational susceptibility to metabolic disorders were found in a mouse model for GDM [104].…”
Section: Epigenetic Effects Of Maternal Obesity and Diabetesmentioning
confidence: 99%
“…Furthermore, methylation-mediated epigenetic mechanisms for intergenerational susceptibility to metabolic disorders were found in a mouse model for GDM [104]. Epigenetic effects of obesity and diabetes on the offspring have in models been shown to occur not only at the fetus level, but also already in the oocyte and sperm [103][104][105][106] implying an influence of both maternal and paternal metabolic disorder [103][104][105][106][107]. Reported DNA methylation changes of maternal metabolic state with putative effects in the brain include, but are not limited to, those on offspring leptin signaling [93,108].…”
Section: Epigenetic Effects Of Maternal Obesity and Diabetesmentioning
confidence: 99%
“…A study of streptozotocin-induced maternal diabetes in mice showed an inhibitory effect of intrauterine hyperglycaemia exposure on the development of brown adipose tissue (BAT) in offspring, thereby impairing the glucose uptake function of BAT in adulthood [40]. The authors found a downregulation of BAT-associated genes, Ucp1 , Cox5b , and Elovl3 , which is accompanied by disorganized ultra-structure of mitochondria in BAT, probably contributing to intracellular lipid accumulation and fat-induced insulin resistance [40]. Another GDM mouse model showed altered DNA methylation patterns in pancreatic tissues, manifested as dyslipidaemia, impaired glucose tolerance, and insulin resistance with advancing age [41].…”
Section: Animal Studiesmentioning
confidence: 99%
“…In agreement with this hypothesis, in the present study, for the first time, we showed that maternal obesity, induced by the CAF diet, can program the ETC of BAT in offspring, resulting in reductions in the expressions of CI and CIII. Similarly, Yu et al 38 have demonstrated that offspring born from diabetic dams present smaller expression of ETC and UCP1 in the BAT due to epigenetic DNA methylation. These findings indicate that the offspring of obese dams have a reduced flow of energetic substrates for oxidative phosphorylation, including lipids, and consequently a lower magnitude of the proton gradient, which is associated with histological characteristics, such as greater lipid deposition, suggesting hypoactivity of thermogenesis.…”
Section: Discussionmentioning
confidence: 83%